The chloroplast genome of the allotriploid, Paeonia × lemoinei cv. Oukan, and its phylogenetic implications - Mingyang Hao; Jiang Wu; Mengyao Wang; Ying Chen; Qi Qiao; Sophie Newmarch; Erqiang Wang; Richard Winkworth; Bingyou Fan (Mitochondrial DNA. Part B. Resources)
The chloroplast genome of Paeonia × lemoinei cv. Oukan, a newly identified allotriploid from Paeonia sect. Moutan, shows typical tree peony features in size, structure, and gene content. A maximum-likelihood phylogenetic analysis revealed cv. Oukan and the known triploid cv. Shouanhong clustered into subsect. Delavayanae and subsect. Vaginatae, respectively. Cv. Oukan is closely related to its maternal parent cv. High Noon, while autotriploid cv. Shouanhong is sister to P. ostii but genetically distinct. This study provides genomic resources and phylogenetic insights for the first allotriploid tree peony, suggesting lineages in both subsects could serve as maternal parents for breeding triploid cultivars.